2020
DOI: 10.3390/agronomy10081118
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of a RD6 Rice Variety for Blast Resistance and Salt Tolerance through Marker-Assisted Backcrossing

Abstract: RD6 is one of the most favorable glutinous rice varieties consumed throughout the north and northeast of Thailand because of its aroma and softness. However, blast disease and salt stress cause decreases in both yield quantity and quality during cultivation. Here, gene pyramiding via marker-assisted backcrossing (MAB) using combined blast resistance QTLs (qBl 1, 2, 11, and 12) and Saltol QTL was employed in solving the problem. To pursue our goal, the RD6 introgression line (RGD07005-12-165-1), containing four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Moreover, under salt stress, the presence of DT-QTLs also promoted seedling growth (Nounjan et al, 2018) of the introgression lines compared to the recipient 'KDML105'. The positive roles on seedling growth under salt stress of the introgressed Saltol QTL containing SKC1 in the genetic background of 'KDML105' and 'RD6' rice were demonstrated by Punyawaew et al (2016) and Thanasrilungura et al (2020), respectively. However, the beneficial roles of SKC1 under drought stress are reported for the first time in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, under salt stress, the presence of DT-QTLs also promoted seedling growth (Nounjan et al, 2018) of the introgression lines compared to the recipient 'KDML105'. The positive roles on seedling growth under salt stress of the introgressed Saltol QTL containing SKC1 in the genetic background of 'KDML105' and 'RD6' rice were demonstrated by Punyawaew et al (2016) and Thanasrilungura et al (2020), respectively. However, the beneficial roles of SKC1 under drought stress are reported for the first time in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Marker-assisted selection was applied in four studies for (1) the selection of parental germplasm in sugarcane breeding programs [18], (2) improving blast resistance and salt tolerance in rice [19], (3) the selection of the pollination constant non-astringent (PCNA) type in Spanish germplasms of persimmon [20], and (4) the selection of resistance to plum pox virus (PPV) in apricot by allele-specific PCR [21]. Wu et al [18] identified two groups among the 150 most widely used sugarcane parental clones.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Based on these results, the authors could identify the most appropriate cultivars to broaden the genetic base of breeding germplasm. Thanasilungura et al [19] improved the rice cultivar RD6 for salt tolerance with the QTL "Saltol" and blast resistance with four different QTLs by marker-assisted backcrossing and phenotypic selection. The authors found that one of the introgression lines showed superior salt tolerance and blast resistance, maintaining higher quality and agronomic performance than RD6.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Compared with drought and flooding, the salinity problem for rice production is rather localized (Saisema and Pagdee, 2015). However, since some farmers are starting to abandon their paddy fields due to severe salinity, the problem has become one of the major issues affecting rice production in Northeast Thailand (Oo et al, 2013;Thanasilungura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%